2013
DOI: 10.1091/mbc.e12-07-0557
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Tre-2/Bub2/Cdc16 (TBC) Rab GTPase-activating proteins

Abstract: Small GTPases control many functions in cells, and the TBC GTPase-activating protein family modulates the activity of the largest G protein subfamily, Rabs. A reconstruction of the evolutionary history of TBC GAPs provides new insight into the evolution of eukaryotic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 56 publications
2
75
0
Order By: Relevance
“…Additional examples include members of the Rab GTPase GAPs, the TBC family. Similar to AGAP, many of the TBC subfamilies (i.e., TBC-F through TBC-N) are found in multiple supergroups, but also seem to be absent from the majority of taxa (Elias et al 2012;Gabernet-Castello et al 2013). More strikingly, there are Rab GAPs and Rab GTPases, for example, TBC-RootA and RabTitan, respectively (Fig.…”
Section: Evolution Of the Endomembrane Systemmentioning
confidence: 93%
See 2 more Smart Citations
“…Additional examples include members of the Rab GTPase GAPs, the TBC family. Similar to AGAP, many of the TBC subfamilies (i.e., TBC-F through TBC-N) are found in multiple supergroups, but also seem to be absent from the majority of taxa (Elias et al 2012;Gabernet-Castello et al 2013). More strikingly, there are Rab GAPs and Rab GTPases, for example, TBC-RootA and RabTitan, respectively (Fig.…”
Section: Evolution Of the Endomembrane Systemmentioning
confidence: 93%
“…For example, the major coat proteins (COPI, COPII, clathrin, adaptins, retromer), Arf GAPs, the small GTPases (Arfs, Sar, Rabs), Syntaxins, EpsinR, and ESCRTs are all found in diverse eukaryotes, indicating once again that the LECA possessed a membranetrafficking system at least as complex as that of most living eukaryotes. Phylogenetic analysis of paralogous protein families such as Syntaxins, Longins, Adaptins, Rabs, Arf GAPs, and TBCs has shown broad conservation of organelle-specific paralogs Doolittle 2002, 2004;Vedovato et al 2009;Hirst et al 2011;Elias et al 2012;Gabernet-Castello et al 2013) suggesting that these are a part of the plesiomorphic state of eukaryotes, adding depth to the deduced level of reconstructed complexity of a membrane-trafficking system in the LECA.…”
Section: A Sophisticated Ancient Membrane-trafficking Machinery and Amentioning
confidence: 99%
See 1 more Smart Citation
“…The GAPs for Rab GTPases contain a TBC Rab-binding domain. 52 Shigella flexneri can resist autophagy-mediated defense in infected epithelial cells and translocates the effector VirA, which is vital for intracellular bacterial persistence, into host cells by a type III secretion apparatus. 53 A recent study 54 demonstrated that VirA possesses TBC-like GAP activity for Rab1, and also found that deletion of VirA and deficiency of GAP activity in Shigella flexneri mutants caused 420% of infected cells to form autophagosomes containing intracellular bacteria.…”
mentioning
confidence: 99%
“…1) have recently been reported. Analysis of both Rab proteins and their TBC-GAPs identified several uncharacterized Rab and Rab-GAP homologs that are ancient but without homologs in humans (Elias et al 2012;Gabernet-Castello et al 2013). Finally, an analysis of the ArfGAP protein family (Schlacht et al 2013) expanded the number of subfamilies from 10 to 11, with the new subfamily (ArfGAPC2) being absent from humans but present in diverse eukaryotic lineages, including plants and important agricultural pathogens like oomycetes.…”
Section: Evolution and Cell Biology Of The Endocytic Systemmentioning
confidence: 99%